Case history of the Fortymile Caribou Herd, 1920-1990 - Patrick Valkenburg; David G. Kelleyhouse; James L. Davis; Jay M. Ver Hoef (Rangifer, 1994)
Early this century, the Fortymile caribou herd was the largest in Alaska and one of the largest in the world. Since the 1940s the herd has remained relatively small, fluctuating between 6000-8000 and about 50 000. To determine possible limiting factors, we reviewed historical fluctuations in herd since and harvest, historical data on wolf numbers and summer and winter weather. The major decline in herd size from 1963 to 1973 was accompanied by high wolf numbers, some years of unfavorable winter and summer weather, and some years of high harvests. From 1974 to 1990 the Fortymile herd failed to recover as well as the adjacent Nelchi-na herd and provided less than one-fourth the harvest despite favorable winter conditions in both areas. Two notable differences between these herds were that (1) wolves were less strongly limited within the range of the Fortymile herd, and (2) moose as alternate prey for wolves remained more abundant within the range of the Nelchina herd.